Estudio fitoquímico y evaluación de las actividades antiinflamatoria y antiproliferativa de extractos de Hydrocotyle bonariensis Lam. (Apiaceae) - Ouviña, Adriana Graciela (2019)
Hydrocotyle bonariensis Lam (Araliaceae) known as "paragüita", "redondita de agua", "tembladerilla? is an authoctonous plant of Argentina that grows in the province of Buenos Aires on the Rioplatense coast. The infusions prepared with aerial parts are used in folk medicine in the treatment of psoriasis and as diuretic, emenagogue and antiseptic. On the other hand, leaves macerated in alcohol are used externally in wounds and inflammatory process of the skin. This work encourage the phytochemical and pharmacological study of the plant in regards to the antioxidant, antiinflammatory and antiproliferative actions which were reported for the first time.\nThe aerial parts of H. bonariesis were collected in the Parque Pereyra Iraola, Province of Buenos Aires . The phytochemical analysis of methanol extract presented a wide phenolic profile, meanwhile the infusion was fractionated by dialysis in order to separate the polysaccharides from the polyphenols. \nIt was demonstrated that the infusion showed absence of acute toxicity and that the carbohydrates participated in the antiinflammatory, in the antioxidant activities, in the modulation of the proliferation of a lymphoma cell line and in the immune modulation of macrophages..\n This work allowed to obtain an integral knowledge of the plant Hydrocotyle bonariensis Lam. and to validate its use as anti-inflammatory and antiproliferative drug.